2016
DOI: 10.1080/13102818.2016.1149038
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and melatonin as biomarkers in patients with giardiasis

Abstract: Giardia is the most frequently reported intestinal parasite worldwide. The aim of this study was to investigate the ghrelin, melatonin, glucose and cholesterol concentration in male patients infected with Giardia lamblia. We enrolled 66 patients with Giardiasis and the control groups consisted of healthy subjects (n D 30). The results demonstrated that there was a significant decrease (P < 0.05) in ghrelin levels, while the melatonin, glucose and cholesterol levels were significantly increased (P < 0.05) in gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In this investigation, samples were compared using the T-test with Graph-Pad Prism version 10 software. A p-value of 0.05 or less is regarded as statistically significant (14,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, samples were compared using the T-test with Graph-Pad Prism version 10 software. A p-value of 0.05 or less is regarded as statistically significant (14,15,16).…”
Section: Discussionmentioning
confidence: 99%
“…18 The present study disagrees with the finding of Ma'ani N et al 17 in Iraq that reported a normal value of HDL in patients with giardiasis, while being consistent with various studies which found higher concentrations of serum HDL in patients infected with G. Lamblia parasite in comparison with the healthy group. 9,18,19,20,23,24 HDL was considered a major carrier in circulation and plays a role in metabolism and transport, and in preventing cholesterol accumulation in the cells of the artery wall. 25…”
Section: Discussionmentioning
confidence: 99%
“…[58], who found in their study in Najaf province where they found I, II, and III with the frequency of 60 %, 25 %, and 15% respectively. These results disagree with findings in other locations of Iraq such asMohammed et al [59] in Baghdad, and Aziz[60] in Wasit who found the dominant genotype is II, and Al-Khanak, and Salman [63] in Wasit who found that genotype III is the dominance.In Egypt, Abdel-Hameed and Hassanein[61] found that genotype II is the most frequent at 87 % and genotype I at 13 % but they do not find genotype III.…”
mentioning
confidence: 85%